Hepatocellular carcinoma: Short‐term reproducibility of apparent diffusion coefficient and intravoxel incoherent motion parameters at 3.0T. Issue 1 (10th January 2014) - Kakite, Suguru; Dyvorne, Hadrien; Besa, Cecilia; Cooper, Nancy; Facciuto, Marcelo; Donnerhack, Claudia; Taouli, Bachir
<x xml:space="preserve">Abstract</x> Purpose To evaluate short‐term test–retest and interobserver reproducibility of IVIM (intravoxel incoherent motion) diffusion parameters and ADC (apparent diffusion coefficient) of hepatocellular carcinoma (HCC) and liver parenchyma at 3.0T. Materials and Methods In this prospective Institutional Review Board (IRB)‐approved study, 11 patients were scanned twice using a free‐breathing single‐shot echo‐planar‐imaging, diffusion‐weighted imaging (DWI) sequence using 4 b values (b = 0, 50, 500, 1000 s/mm2) and IVIM DWI using 16 b values (0–800 s/mm2) at 3.0T. IVIM parameters (D: true diffusion coefficient, D*: pseudodiffusion coefficient, PF: perfusion fraction) and ADC (using 4 b and 16 b) were calculated. Short‐term test–retest and interobserver reproducibility of IVIM parameters and ADC were assessed by measuring correlation coefficient, coefficient of variation (CV), and Bland–Altman limits of agreements (BA‐LA). Results Fifteen HCCs were assessed in 10 patients. Reproducibility of IVIM metrics in HCC was poor for D* and PF (mean CV 60.6% and 37.3%, BA‐LA: −161.6% to 135.3% and −66.2% to 101.0%, for D* and PF, respectively), good for D and ADC (CV 19.7% and <16%, BA‐LA −57.4% to 36.3% and −38.2 to 34.1%, for D and ADC, respectively). Interobserver reproducibility was on the same order of test–retest reproducibility except for PF in HCC. Reproducibility of diffusion parameters was better in liver parenchyma compared to HCC. Conclusion Poor reproducibility of D*/PF and good reproducibility for D/ADC were observed in HCC and liver parenchyma. These findings may have implications for trials using DWI in HCC. J. Magn. Reson. Imaging 2015;41:149–156. © 2014 Wiley Periodicals, Inc.